Plan de promoción de la finca agroturístico en la Finca Quinta "K" para el desarrollo turístico del cantón valencia, Año 2019 - Reinoso Gómez, Dayanna Estefanía (2019)
This research project arises from the need for tourism management around the farm "Quinta k", Oasis enclosure, of Valencia currently has problems of insipience tourist information of the place that tourists endow their visit, this research aims to prepare the proposal for a plan of tourism promotion at Farm Agrotourism "Quinta k" for tourism development in the canton Valencia province of Los Rios. Likewise, the following methods were used for the analysis of information: Diagnostic and empirical; together the observation techniques, surveys and interviews with the inhabitants of the sector and the canton of Valencia; The respective formula of Canaves was also used to determine the total number of slopes resulting in 381 people to be surveyed, consisting of 10 closed questions in order to identify for which segment the project is directed, to meet the needs of tourists who practice Nature tourism looking for new spaces for relaxation and distraction. Finally, it was obtained as a result that people do not know the “Quinta k” farm property due to the lack of tourist promotion of the place of study as well as that by implementing a promotional plan it will contribute to the tourism and socio-economic development of the community and in the surrounding areas, thanks to the surveys, it was possible to verify that the project is viable and meets the hypothesis proposed in the investigation. In this design work a logo, slogan, leaflets and a Fan page on Facebook that can be visualized by social networks, Smartphone and Tablet about everything that offers the farm "Quinta k". To finish the farm with several tourist products including: CCN 51 cocoa crops, estuary, sports fields, recreation and camping area that will contribute to the economic benefit for the community and surrounding areas. Keywords: Tourism development, promotion plan, agritourism farm, agritourism